Acceleration Profile of Elite Gaelic Football Match Play. Issue 3 (March 2018) - Ryan, Martin; Malone, Shane; Collins, Kieran
Abstract : Abstract: Ryan, M, Malone, S, and Collins, K. An acceleration profile of elite Gaelic football match play. J Strength Cond Res 32(3): 812–820, 2018—The use of global positioning system (GPS) technology in Gaelic football is the primary source of quantifying game demands. The aim of this study was to quantify the acceleration profile of elite Gaelic football. Thirty-six elite male Gaelic football players (mean ± SD, age: 24 ± 6 years; height: 180 ± 7 cm; mass: 81 ± 7 kg) across 5 playing positions took part in a multiple study ( n = 154 observations). Player movement was recorded during 19 ( n = 19) competitive games over 2 seasons using 4-Hz GPS (VXSport, New Zealand). The average total distance (m), high-speed running distance (m; ≥17 km·h −1 ), and very high–speed running distance (m; ≥22 km·h −1 ) were recorded. In addition, the number ( n ), distance (m), and the duration of accelerations were quantified. Accelerations were subdivided into 14 equal parts of 5-minute epochs (E1 = 0–5 minutes, E2 = 5–10 minutes, E3 = 10–15 minutes etc). Players performed 166 ± 41 accelerations. High-speed running distance and very high–speed running distance was 1563 ± 605 and 524 ± 190 m, respectively. The mean acceleration distance was 267 ± 45 m distributed between 12 ± 5 accelerations per 5-minute epoch. The maximum acceleration epoch classified as the greatest distance covered accelerating during a predetermined 5-minute epoch was 296 ± 134 m. The PEAK epoch resulted in a significant reduction of acceleration distance covered in the period before and in the subsequent epoch. An understanding of the acceleration profile in Gaelic football can inform the prescription of appropriate training regimen.